👤


[tex](\frac{1}{ \sqrt{3} } + \frac{1}{ \sqrt{2} } ) \times \sqrt{6} - \frac{1}{ \sqrt{5} } + \frac{1}{ \sqrt{3} } \times 15[/tex]
[tex] + ( \frac{1}{ {2}} - \frac{1}{ \sqrt5} ) \times \sqrt{10} [/tex]
repede va rog​


Răspuns :

Explicație pas cu pas:

( 1 / √3 + 1 / √2 ) · √6 - 1 / √5 + 1 / √3 · 15 + ( 1 / 2 - 1 / √5 ) · √10 =

= ( √3 / 3 + √2 / 2 ) · √6 - √5 / 5 + √3 / 3 · 15 + ( 1 / 2 - √5 / 5 )  · √10

= ( 2√3 / 6 + 3√2 / 6 ) · √6 - √5 / 5 + √3 / 3 · 15 + ( 5 / 10 - 2√5 / 10 ) · √10

= ( √3 / 3 + √2 / 2 ) · √6 - 1 √5 / 5 + √3 / 3 · 15 + ( 1 / 2 - √3 / 3 ) · √10

= √18 / 3 + √12 / 2 - √5 / 5 + 5√3 + √10 / 2 - √30 / 3

= √2 + √3 - √5 / 5 + 5√3 + √10 / 2 - √30 / 3

= √2 + 6√3 - √5 / 5 + √10 / 2 - √30 / 3